Contemporary Patient Satisfaction Rates for Three-Piece Inflatable Penile Prostheses. (26th July 2012) - Bernal, Raymond M.; Henry, Gerard D.
Abstract : Among the many treatments for erectile dysfunction, implantation of a penile prosthesis has been associated with high patient satisfaction rates. Specifically, the placement of a three-piece inflatable penile prosthesis (IPP) confers the highest rates of satisfaction. We reviewed the literature over the past 20 years regarding satisfaction rates for penile prostheses, with a focus on patients who had undergone an initial IPP implantation for erectile dysfunction. In all, 194 articles were reviewed, and of these, nine met inclusion criteria for analysis and data collation. We determined contemporary satisfaction rates to reflect patients' experiences with newer products and surgical approaches. Of importance, we noted that varied metrics were used to determine patient satisfaction, and overall satisfaction could not be precisely determined. Nevertheless, we found that patients in general were quite satisfied with their three-piece IPPs and restoration of sexual function. We also identified reasons for patient dissatisfaction and reviewed the literature to find ways by which satisfaction could be improved. Given the various means by which patient satisfaction was determined, future efforts should include standardized and validated questionnaires.